1992
DOI: 10.1111/j.1471-4159.1992.tb09309.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Effects on Inositol Phospholipids and Inositol Phosphates: Evaluation of an In Vivo Model for Assessing Polyphosphoinositide Turnover in Brain

Abstract: Administration of lithium chloride to rats injected intracerebrally with [3H]inositol led to time- and dose-dependent increases in levels of labeled inositol monophosphates in brain. Quantitative analysis of the inositol phosphates by ion chromatography revealed 37- and 20-fold increases in the mass of myo-inositol 1-phosphate and 4-phosphate, respectively, at 4 h intraperitoneal after injections of 6 mEq/kg of lithium chloride. Albeit to a much lesser extent, lithium administration also resulted in an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
(23 reference statements)
3
14
0
Order By: Relevance
“…Animal studies have shown that, in vitro and in vivo, lithium administration leads to a decrease in myo-inositol and an increase in the inositol monophosphate precursors (Sherman et al, 1985;Godfrey et al, 1989;Hirvonin, 1991;Sun et al, 1992). Adding to these findings we have found that in animals sodium valproate also decreases the concentration of myo-inositol and increases the concentration of inositol monophosphates in rat brain, suggesting the possibility of a similar mechanism of action (O'Donnell et al, 2000).…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Animal studies have shown that, in vitro and in vivo, lithium administration leads to a decrease in myo-inositol and an increase in the inositol monophosphate precursors (Sherman et al, 1985;Godfrey et al, 1989;Hirvonin, 1991;Sun et al, 1992). Adding to these findings we have found that in animals sodium valproate also decreases the concentration of myo-inositol and increases the concentration of inositol monophosphates in rat brain, suggesting the possibility of a similar mechanism of action (O'Donnell et al, 2000).…”
Section: Introductionmentioning
confidence: 50%
“…One other point to note is that a decrease in myoinositol is often seen in rat studies following lithium treatment (Sherman et al, 1985;Godfrey et al, 1989;Hirvonen 1991;Sun et al, 1992) and we have recently found decreased myo-inositol concentrations in rats following both lithium and valproate treatment (O'Donnell et al, 2000). However, it is possible that these differences may be explained by the fact that these are ex vivo studies which firstly may have higher sensitivity than the in vivo studies and secondly may use significantly higher doses of medications than those used in human studies.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years several lines of investigation have lent support to this hypothesis. Numerous studies performed in various cell systems, in both cells and the brain, have demonstrated lithium-induced effects on the receptor-mediated P1 hydrolysis pathway, including decreased cellular inositol levels (Allison et al, 1976) and significantly elevated levels of IPs (Dixon et al, 1992;Sun et al, 1992;Atack et al, 1993;Ishima et al, 1993), CMP-PA (Godfrey, 1989;Kennedy et al, 1990;Watson et al, 1990;Atack et al, 1993;Stubbs and Agra-noff~1993;Jenkinson et al, 1994;Lenox and Watson, 1994), phosphatidic acid, and DAG (Drummond and Raeburn, 1984;Downes and Stone, 1986;Brami et a!., 1991Brami et a!., , 1993 (for review, also see Manji et al, 1995). The IC.~0 of lithium for IMPase (0.8 mM) is within the range (0.6-1.2 mM) of therapeutic plasma lithium levels required for treatment of affective disorders (Hallcher and Sherman, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this indicates that Wnt-3a utilizes alternate pathways, in addition to the canonical pathway to inhibit cell proliferation, or that LiCl is not as efficacious as Wnt-3a is unclear. LiCl may also have other cellular effects, such as increasing inositol lipids, which may influence its efficacy in this assay [53]. These data do suggest, however, that Wnt-3a can inhibit proliferation of MEMM cells, in part, through control of b-catenin levels.…”
Section: Cross-talk Between Tgfb and Wnt-3a In Regulation Ofmentioning
confidence: 99%